L’intégration des TIC dans la séquence pédagogique en espagnol : le concept d’espace langue - Denis Lucchinacci (ALSIC: Apprentissage des Langues et Systèmes d'Information et de Communication)
How can we help our pupils to take a more active part in their learning? How can we provide the conditions of a valuable "apprenticeship" which will act as an incentive to profitable learning? In order to find an answer to those questions, I have set up at the Lycée Jean Jaurès in Saint- Affrique a pedagogical "structure" offering the various technological means available today to language teachers. In this new teaching structure, the pupils, within the normal course of a language lesson, can secure and develop basic "know-how" and knowledge in a more autonomous way, at their own pace. This structure cannot be considered as a free-access system. It will be integrated by the teacher in the normal curriculum. Every pupil will then be at the same time a researcher and a learner, since the results of each research will eventually be used by the whole class, allowing everybody to test their own level of knowledge and know-how. Naturally, each pupil must be allowed to choose the teaching media they like better - video recordings, Internet, audio recordings, plain printed matter - and consequently the teacher has a different role to play. He will thus act as an advisor who can adjust himself to the needs of pupils who play an active part in their learning